Geographical variation in reporting Interstitial Lung Disease as an adverse drug reaction: findings from an European Medicines Agency analysis of reports in EudraVigilance. Issue 6 (22nd March 2016) - Pinheiro, Luis; Blake, Kevin; Januskiene, Justina; Yue, Qun‐Ying; Arlett, Peter
Abstract: Purpose: Clinically, interstitial lung disease (ILD) is a heterogeneous group of over 150 respiratory disorders. In the context of its signal evaluation work, the European Medicines Agency's (EMA) Pharmacovigilance Risk Assessment Committee (PRAC) has seen geographic clustering of case reports of ILD from Japan. To explore this further, EudraVigilance (EV), the EMA's database of adverse drug reactions (ADRs), was analysed. The results have been used to inform on implications for pharmacovigilance including signal detection and evaluation activities. Methods: EV was queried for reports of respiratory ADRs coded using MedDRA for the period 1994–2014 for all medicinal products. Descriptive statistics and non‐parametric (chi‐square) independence tests were produced to compare reporting of ILD from Japan versus the rest of the world. Results: As of 31 December 2014, there were 26 551 case reports of ILD in EV of which 17 526 (66%) originated in Japan. The reporting rate of ILD for Japan has been consistently higher over the period. The odds that a case report from Japan in EV refers to ILD is OR = 20.7, 95% CI 20.2, 21.3 ( p  < 0.001), compared to OR = 0.60, 95% CI 0.54, 0.67 ( p  < 0.001) for pulmonary fibrosis. Conclusions: A geographic imbalance between Japan and the rest of the world in reporting respiratory ADRs as ILD is confirmed. Consequently, the PRAC has developed approaches to address this in relation to signals of ILD it assesses to allow for more targeted risk minimisation including updates to the product information in the EU setting. Copyright © 2016 John Wiley & Sons, Ltd.